Показники транскордонного туризму України та Польщі - Бучко, Жанна; Меленко, Яна (Чернівці: Чернівецький національний університет, 2015)
Досліджено процеси та динаміку транскордонного співробітництва України та Польщі в галузі туризму. Основна увага приділена аналізу динаміки туристичних потоків між Україною та Польщею впродовж останніх десяти років. Проаналізовано показники виїзного та в’їзного туризму України та Польщі, визначені пріоритетні країни-дестинації за обома показниками та сучасні тенденції на ринку туристичних послуг у рамках транскордонного співробітництва. Визначено основні перешкоди, перспективи та переваги транскордонної співпраці між Україною та Польщею в галузі туризму.
Quantitative Indicators of Transboundary Tourism in Ukraine and Poland
The importance of transboundary tourism research it Ukraine-Poland border is a direct consequence of increased tourist flow between the two countries. Poland as a country is an intermediary in the process of Ukraine-EU integration. This means, that in the process of inclusion of Ukraine in the European community, Poland represents Ukrainian interests and plays active role in improving all kinds of Ukrainian state policies, in particular polices related to tourism. Tourism-related interaction between the two countries is growing continually, which motivates systematic and detailed analysis of different tendencies of the local tourism services market established as the part of the transboundary relations. The goal of writing this manuscript is establishing key tendencies of Ukrainian-Polish transboundary tourism marked, which requires analysis of the statistical data on Ukrainian-Polish tourist flow by identifying the primary sources countries of incoming tourists and the primary tourism destination countries in Poland and Ukraine. The methodology of our work relies on systematization and synthesis of the statistical data about Ukrainian-Polish tourist flows. Quantitative characteristics of the inbound and outbound tourism flows in Ukraine and Poland are illustrated in several tables and figures. Results. The authors studied the processes of transboundary collaboration between Ukraine and Poland and the dynamics thereof, determining several important tendencies related to this tourism. The main attention was focused on the analysis of the dynamics of tourist flow between Ukraine and Poland during the last decade and on the analysis of inbound and outbound tourism in the two countries. The authors showed that international tourist travel of Polish residents to other European destinations includes Ukraine. The main international destination for Polish tourists is Germany (over 2 million visits annually), whereas Ukraine was the destination for about 300 thousand Polish tourists. The total number of international trips originating in Poland in 2013 was over 11.4 million, increasing almost by 5 million trips in comparison to 2005. The most significant decline relative to the general trend (by almost 1.3M trips) was detected in 2008-2009, likely, because of the economic recession. Overall, our analysis shows that the international tourist is strongly influenced by economic and political factors. Other results included in the paper include the list of the most popular destinations for Polish tourists (Germany, Czech Republic, Austria, Italy, and The Netherlands) and the list of the least popular among the typical destinations (USA, Belarus, Russia, Denmark, and Bulgaria). The main source countries of inbound tourists for Poland are Ukraine, Belarus, and Russia, and among EU countries: the UK and Germany. For Ukraine, the main tourist source countries are Russia and Poland, followed by Moldova, Belarus, Romania, Hungary, and Slovakia. For Ukrainian tourists, ten main outbound destinations include Russia, Poland, Belarus, Moldova, Hungary, Romania, Turkey, Slovakia, Egypt, and Germany. In 2009, Ukrainian international tourism decreased by half because of the unfolding world economic crisis that year. Even though Russia was the main destination for Ukrainian tourists since 2006, in 2012 the leading destination shifted to Poland. The 2014 number of 4.6M visits to Russia is the lowest during the studied period: even in 2009 this number was higher by 0.3M. This sharp decrease is clearly explainable by the increasing military conflict in the Eastern Ukraine near the border with Russian Federation. The novelty of our work is the determination of main tendencies and problems of the last decade in the international Ukrainian-Polish collaboration in the area of tourism. The practical importance of the presented research is in the possibility of incorporating its results into outlining the main strategies and plans for developing tourism in Ukraine and Poland. Key words: transboundary tourism, transboundary collaboration, European region, tourist flow, inbound tourism, outbound tourism, tourist destination.
Keywords: Транскордонний туризм; транскордонне співробітництво; єврорегіон; туристичні потоки; туристична дестинація; в’їзний туризм; виїзний туризм